Experimental Research of the Influence of Microfracture Morphology on Permeability of Shale Rock - Xiaohe Huang; Yunqian Long; Yuyi Wang; Ming Yue (Geofluids)
Hydraulic fracturing is currently one of the main technical methods of shale gas exploitation. The permeability variation of shale gas reservoir after fracturing is inevitable, while the influence of fracture length and fracture width on permeability and seepage characteristics of shale rock is a mystery. Besides, the stress sensitivity characteristics of shale rock, derived from different initial permeability, with the same permeability after fracturing are also ambiguous. To this end, a series of seepage characteristic experiments related to different fracture parameters are carried out with the black shale of the Longmaxi Formation in Sichuan gas field as the research target. The results show that the fracture length and fracture width have a good exponential relationship with the corresponding permeability of the reformed shale rock, and the contribution of the fracture width to shale permeability is much greater than that of the fracture length. In addition, the nonlinear seepage characteristics of shale rock are gradually significant with the reduction of fracture length and fracture width. Taking the primitive effective stress (10 MPa) as a critical point, the permeability of shale with large initial permeability decreased by 26.4%, which is about twice as much as that of shale rock with small initial permeability (14.9%) in the selected pressure loading stage, owing to the difference of fracture width inside the shale rock. The permeability of the shale rock with a large initial permeability is restored by 14.7%, while the shale rock with a small initial permeability is only recovered to 5.2% in the pressure unloading stage, which is attributed to the closure of fractures, especially the loss of fracture width. This research can provide some new insights for the production prediction of shale gas reservoir after fracturing.